Theoretical and Experimental Reactivity Predictors for the Electrocatalytic Activity of Copper Phenanthroline Derivatives for the Reduction of Dioxygen - Zagal-Moya, J; Zagal-Moya, J; Lemus-Chavez, L; Lemus-Chavez, L (American Chemical Society, 2019)
We have systematically studied the catalytic activity of a series of substituted bisphenanthroline Cu complexes adsorbed on glassy carbon electrodes for the oxygen reduction reaction (ORR) in aqueous media. The aim of this work is to test reactivity descriptors for ORR previously proposed for MN4 complexes. As the active site is the Cu(I) center, the foot of the wave for O2 reduction on electrodes modified with Cu bisphenanthrolines appears at potentials very close to the [Cu(II)phen2]ad ++ + e- ⇆ [Cu(I)phen2]ad + redox process. Generally, the catalytic activity as (log i)E versus the ECu(II)/(I)° redox potentials follows a linear correlation with a slope close to +0.120 V/decade, where the activity increases as the ECu(II)/(I)° becomes more positive. This indicates that electron-withdrawing substituents on the ligand favor the reaction by shifting the ECu(II)/(I)° to more positive values, making the Cu center more noble. This shift in the ECu(II)/(I)° is essentially an electronic effect. However, another way to stabilize the Cu(I) state is by placing groups on the ligand that hinder the [Cu(II)square-planar]ad ++/[Cu(I)tetrahedral]ad + change. We have found that this steric effect seems to be more prominent than the electronic effects caused by electron-withdrawing groups and the increase in the catalytic activity for ORR is more pronounced. Copyright © 2019 American Chemical Society.